Evaluación de la aplicación de la NIC 16 en la empresa Colombatti S.A, de la ciudad de Babahoyo, periodo 2022. - Castro Hernández, John Jairo (2023)
This case study deals with the Evaluation of the application of IAS 16 in the company Colombatti S.A, in the city of Babahoyo, period 2022. The main objective of the research is to evaluate compliance with IAS 16, since the Standards International Accounting Standards (IAS) are globally known guidelines that must always be present in the financial statements of any company, in order to reflect the situation of the companies' financial operations. IAS 16 ensures that PPE assets are appropriately valued in the financial statements, which will better reflect their true value and contribute to the accuracy of financial reporting. The study has a non-experimental design and the approach is mixed. The types of research are: documentary and field. The techniques applied were two: observation and interview, the first was carried out directly to the financial statements and enabling accounting information, while the second was carried out through a guide of five semi-structured questions. The results allowed us to conclude that: The company Colombatti S.A does not effectively comply with the provisions of IAS 16 with respect to the registration of property, plant and equipment accounts because the staff does not have the knowledge regarding the accounting standards for an appropriate treatment of financial information, this is one of the reasons why the organization faces various inconveniences in relation to the accounting treatment of fixed assets.